2013
DOI: 10.1371/journal.pone.0056686
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Proteome Exploration to Provide a Resource for the Study of Agrocybe aegerita

Abstract: Background Agrocybe aegerita, the black poplar mushroom, has been highly valued as a functional food for its medicinal and nutritional benefits. Several bioactive extracts from A. aegerita have been found to exhibit antitumor and antioxidant activities. However, limited genetic resources for A. aegerita have hindered exploration of this species.Methodology/Principal FindingsTo facilitate the research on A. aegerita, we established a deep survey of the transcriptome and proteome of this mushroom. We applied hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 110 publications
(132 reference statements)
3
53
2
Order By: Relevance
“…Among the up-regulated pathways in S1-Pri, we are particularly interested in novel signaling pathways [62]. Two up-regulated genes in S1-Pri were assigned to the mTOR signaling pathways, and real time PCR confirmed the 5 â€Č -SAGE observations for these two DEGs (CC1G_10718 & CC1G_00269).…”
Section: Resultsmentioning
confidence: 93%
“…Among the up-regulated pathways in S1-Pri, we are particularly interested in novel signaling pathways [62]. Two up-regulated genes in S1-Pri were assigned to the mTOR signaling pathways, and real time PCR confirmed the 5 â€Č -SAGE observations for these two DEGs (CC1G_10718 & CC1G_00269).…”
Section: Resultsmentioning
confidence: 93%
“…The contig size distribution revealed that more than half of the ESTs (32,602; 89.4%) were between 200 and 1000 bp in length (Table 2). The GC content of A. polytricha ESTs was 61.31%, which was much higher than L. edodes (48.31%) and A. aegerita (approximately 53%) [11], [14]. GC content analysis revealed that A. polytricha transcripts have a high GC content similar to the Auricularia delicata genome (58.6%).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, two recent gene expression studies in two other Agaricomycotina species allowed a large-scale comparison of transcript levels in the vegetative mycelium and fruiting bodies. In Agrocybe aegerita, Wang et al (2013) found one putative MIP (AA_35507 ; Table S6 of supporting information) being upregulated in fruiting bodies, which shows high homology to aquaglyceroporins from L. bicolor (data not shown). In Coprinopsis cinerea, expression of a putative aquaglyceroporin-encoding gene (CC1G_11437T0; file 1 of supporting information) could only be detected in the primordial stage of fruiting bodies but not in the vegetative mycelium (Cheng et al 2013).…”
Section: Filamentous Fungimentioning
confidence: 99%